Analisis Perbandingan Kualitas Produk, Strategi Promosi Dan Persepsi Konsumen Antara Toko Putri Agata Dan Putri Idris Di Kota Bima - Nurhaidah; Ismunandar (Pusat Riset dan Inovasi Nasional, 2024)
Abstract. This study aims to determine whether there are significant differences in product quality, promotion strategies and consumer perceptions between Putri Agata and Putri Idris stores in Bima City. This type of comparative research with primary data in and sourced from the research instrument in the form of a Likert-scale questionnaire so that the type of data used is quantitative data. The population used in this study is all consumers who have visited Putri Agata's shop and have visited Putri Idris' shop in Bima City whose number is unknown (Unknown Population). The sample in the comparative study was 30 people for each object or research subject, so that the total sample size was 60 respondents consisting of 30 respondents at Putri Agata Shop and 30 respondents at Putri Idris Shop in Bima City. Data were collected by observation, questionnaires and literature study. Data analysis techniques using validity test, reliability test and Independent Sample Test. The results showed that there were significant differences in product quality, promotion strategies and consumer perceptions between Putri Agata and Putri Idris Stores in Bima City.